2021
DOI: 10.3389/fpls.2020.615547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Gibberellin, Paclobutrazol, Abscisic Acid, and Ethrel Application on Bulblet Development in Lycoris radiata

Abstract: Lycoris species have great ornamental and medicinal values; however, their low regeneration efficiency significantly restricts their commercial production. Exogenous hormone application is an effective way to promote bulblet development, but their effect on Lycoris radiata has not been verified to date. In the present study, we examined the effect of different exogenous hormones on bulblet development in L. radiata, and found that gibberellic acid (GA) significantly inhibited, whereas paclobutrazol (PBZ), absc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Kinetin is an unnatural cytokinin to improve plant stress resistance and delays aging (Nesmith et al, 2005 ; Lukatkin et al, 2007 ). These and other growth regulators have been applied to various crops (Oshanova et al, 2021 ; Wang J. et al, 2021 ; Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kinetin is an unnatural cytokinin to improve plant stress resistance and delays aging (Nesmith et al, 2005 ; Lukatkin et al, 2007 ). These and other growth regulators have been applied to various crops (Oshanova et al, 2021 ; Wang J. et al, 2021 ; Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, we found that an initial relatively low level of ABA might be favorable for effective bulblet regeneration in vitro. This difference might result from the different first sampling time points (3 d after cross-cutting by Xu (2021) [ 33 ] versus 1 d in this study), indicating that the changes in endogenous hormones are rapid and significant regarding regulation during the competence stage (0–1 d). ZR is the most abundant CK in plants [ 34 ], exhibiting cell division and meristematic activities during plant growth and development.…”
Section: Discussionmentioning
confidence: 91%
“…Exogenous hormone application is an effective way to promote bulblet development. Xu (2021) examined the effect of different exogenous hormones on bulblet development in L. radiata ex vitro and reported that GA significantly inhibited bulblet development, whereas paclobutrazol (PBZ), ABA, and Ethrel had positive effects [ 33 ]. In contrast, we found that an initial relatively low level of ABA might be favorable for effective bulblet regeneration in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations